3D printing cultures, politics and hackerspaces - Savvides, Leandros (Emerald Publishing Limited, 2021)
This stand-out book appreciably contributes to growing debates within Science and Technology Studies concerned with cultural politics, the emergence of citizen science and civil society interventions in shaping technology. By drawing on fieldwork data, Savvides examines the bourgeoning 3D printing culture outside the professional lab in Hackerspaces, Makerspaces and Fab Labs. This engaging ethnography not only builds arguments on tracing the historical roots of makers and Hackerspaces, 3D printing technology and political narratives surrounding these new technological environments; it also illustrates how 3D printing has configured parallel grassroots innovation in experimental spaces in the UK, Germany and Cyprus and brought together hobbyist maker communities, activists and entrepreneurs alike. The study also addresses the convergence of activism and the maker culture with prevalent cultural imaginaries - such as the visionary creator within decentralized and distributive manufacturing, the idea of autopoietic social systems, or the imaginative leap to space colonization - and touches upon challenges and motivations in the field of grassroots innovation by examining how it';s organized and conducted in semi-informal contexts.
Keywords: Three-dimensional printing -- Social aspects.; Makerspaces.; Science -- Social aspects.; Social Science, Technology Studies.; Cultural studies.; elektronické knihy; electronic books